Increasing Engagement for Young Children With Autism Spectrum Disorder Using Way to Play: A Preliminary Investigation of the Adult Training Program. Issue 2 (13th December 2021) - Beaumont, Dervla; Blakey, Tanya; Stuart, Neil; Woodward, Julia
Abstract: Way to Play is an approach that supports adults to promote the engagement of young children with autism spectrum disorder through play. The Ministry of Education in New Zealand has collaborated with Autism New Zealand to ensure the sustainable delivery of Way to Play within Auckland's early learning services by training early intervention staff to both use Way to Play and to coach and support other adults in its use. Key strategies that form the foundation of Way to Play are described, and an outline of the evidence base for these strategies is provided. Preliminary data demonstrate the effectiveness of the training approach and the perceived impact for young children with autism and their parents/carers and teachers. Case examples illustrate how Way to Play is used across home and educational settings to successfully support the engagement and inclusion of young children with autism. Suggestions are made for a comprehensive investigation of program effectiveness.